The Inovation In Teaching Balinese And Javanese Dances In English For Students Of Dance Departement - Dewi Yulianti, Ni Ketut; Widyarto, Rinto; Yuliasih, Ni Ketut (Mudra Jurnal Seni Budaya, 2016)
Creating an innovation in teaching Balinese and Javanese dances in English for the students of Dance department who learn English is an interesting and effective Way. This innovation has given a significant result that the students of Dance department have been able to explain the basic Balinese and Javanese dances movements in English after translating the existence of Balinese and Javanese dances and all terms related to them from Indonesian into English. This idea becomes one of the efforts to strengthen the steps of Indonesian Institute of the Arts (ISI) Denpasar in the international level and in reaching the vision to be the centre of excellent. There are three main discussions in this paper, namely, the existence of Balinese dance, the exsistence of Javanese dance, and teaching method in teaching Balinese and Javanese dances. The existence of Balinese and Javanese dances and some terms and terminologies associated with Balinese and Javanese dances and other things that are still relevant are described in the result ofthis study. It is very signiï¬cant benefit in the teaching-learning process of English and of Balinese and Javanese dances as well This paper is a part of the result of competitive research grants funded by ISI Denpasar DIPA Number : DIPA-023-O4.1.673453/2015 dated November l4, 2015. The other result of this research has also been presented in the 6th International Seminar on Austronesia Languages and Literatures, Udayana University, Denpasar dated 28-29 Agustus 2015 The method apllied is the translation research methods combined with dance research method, which is started with collecting the terms related to Balinese and Javanese dances , then translated into English. Furthermore, the translation results are tested in teaching dance to students majoring in Dance department and foreign students who studied at ISI Denpasar . Key words : innovation , teaching , Balinese and Javanese dances , dance department